2012
DOI: 10.1242/jeb.067264
|View full text |Cite
|
Sign up to set email alerts
|

Odorant tuning of olfactory crypt cells from juvenile and adult rainbow trout

Abstract: SUMMARYTeleost fish lack independent olfactory organs for odorant and pheromone detection. Instead, they have a single sensory epithelium with two populations of receptor neurons, ciliated and microvillous, that are conserved among vertebrates, and a unique receptor cell type named the olfactory crypt cell. Crypt cells were shown to be chemosensory neurons that project to specific areas in the olfactory bulb, but their odorant tuning and overall function remain unclear. Reproduction in fish is generally synchr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 57 publications
1
38
0
2
Order By: Relevance
“…Crypt cells are relatively sparse compared to other OSNs (Hansen and Finger, 2000; Schmachtenberg, 2006) and, in zebrafish, appear to be nearly homogenous in their expression of the olfactory receptor gene, ora4 (Oka et al, 2012). Ligands for the Ora4 receptor are unknown, although there is evidence in the trout that crypt cells are most sensitive to sexual pheromones (Vielma et al, 2008; Bazaes and Schmachtenberg, 2012). The restricted expression of lhx2a coupled with the fact that ~10% of OSNs are ora4 negative, suggests that crypt cells are a diverse population and that the Ob-Ha pathway may sense a distinct odorant cue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crypt cells are relatively sparse compared to other OSNs (Hansen and Finger, 2000; Schmachtenberg, 2006) and, in zebrafish, appear to be nearly homogenous in their expression of the olfactory receptor gene, ora4 (Oka et al, 2012). Ligands for the Ora4 receptor are unknown, although there is evidence in the trout that crypt cells are most sensitive to sexual pheromones (Vielma et al, 2008; Bazaes and Schmachtenberg, 2012). The restricted expression of lhx2a coupled with the fact that ~10% of OSNs are ora4 negative, suggests that crypt cells are a diverse population and that the Ob-Ha pathway may sense a distinct odorant cue.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that subcomponents of complex odorants such as fish flakes or conspecific extract masked or antagonized an activating cue (e.g., specific amino acids). Purified amino acids and specific components of sexual pheromones have been shown to elicit responses in the crypt cells of other fish species (Vielma et al, 2008; Bazaes and Schmachtenberg, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…A large majority of crypt cells respond to only one category of odorants. Intracellular recordings and calcium imaging studies carried out on mackerel and juvenile trout showed that different subsets of crypt cells respond either to amino acids, bile acids, or reproductive pheromones (Schmachtenberg, 2006; Vielma et al, 2008; Bazaes and Schmachtenberg, 2012). However, in mature trout, the majority of crypt cells respond to reproductive pheromones of the opposite sex and not to the other categories, indicating a change in the response profile of crypt cells during life, depending on sexual maturity and sex of the fish (Bazaes and Schmachtenberg, 2012).…”
Section: Olfactory Epitheliummentioning
confidence: 99%
“…Interestingly, transgenic studies in zebrafish revealed that ciliated OSNs do not share glomeruli with microvillous OSNs (Sato et al, 2005(Sato et al, , 2007 and recently, chondroitins were shown to be potent alarm substances that activate a mediodorsal locus in the zebrafish olfactory bulb (Mathuru et al, 2012), which is also activated by sex pheromones (Friedrich and Korsching, 1998). The mediodorsal region is innervated by crypt neurons expressing one type of receptor (Ahuja et al, 2013), which was reported to be activated by multiple ligands (Bazaes and Schmachtenberg, 2012;Vielma et al, 2008). Therefore, it might be that H3NO-and TLC-sensitive neurons express the same type(s) of receptor, but differentiate with respect to function and subcellular machinery.…”
Section: Discussionmentioning
confidence: 99%